Metaproteomics Profiling of Gut Microbiota in Pediatric Acute Lymphoblastic Leukemia Patients - Ezz El Din, Shahd (AUC Knowledge Fountain, 2023)
The gut microbiota is the collection of microorganisms that harbor the human gastrointestinal tract. The relation of microbiota and cancer is an emerging field as several studies have linked the gut microbiota to cancer. Such findings opened the door towards a new era of studies aiming to reveal the role of the microbiota in cancer initiation and progression. Although several metagenomic studies have provided insights into the gut microbial composition in health and diseased state, the microbial functional characteristics is still poorly understood. With current advances in mass spectrometry, comprehensive understanding of microbiota proteome became possible. In this vein, the objective of this study was to explore the gut microbial composition in stool samples from pediatric acute lymphoblastic leukemia (ALL) patients, compared to the non-cancerous profile. The ALL is one of the most common pediatric cancer worldwide accounting for 25% of all childhood cancer cases, and identify the microbial proteins, and their functional implications in pediatric ALL patients. The microbiota profiling analysis revealed the microbial composition in the stool of ALL patients, including the high abundance of some genera such as Bacteroides, Prevotella, and Streptococcus, compared to other less abundant organisms, such as Blautia, Lachnospiraceae, Roseburia. Additionally, the metaproteomics results inferred the functional implications of the gut microbiota in ALL. The results pinpointed higher iron demand and oxidative stress in the stool of ALL patients compared to healthy individuals. Furthermore, functions related to amino acid, carbohydrate and butyrate metabolism were downregulated in ALL. These promising results are preliminary step toward a deeper understanding of the gut microbiota in ALL.